Thromboembolic events in patients with paroxysmal nocturnal hemoglobinuria (PNH): Real world data of a Greek nationwide multicenter retrospective study - Chatzileontiadou, S.; Hatjiharissi, E.; Angelopoulou, M.; Asimakopoulos, J. V.; Loutsidi, N. E.; Chatzikonstantinou, T.; Zikos, P.; Bouchla, A.; Bezirgiannidou, Z.; Kouvata, E.; Frouzaki, C.; Chaloudis, P.; et al. (Frontiers in Oncology, 2023)
Thrombosis is the most common and a life-threatening complication in patients with Paroxysmal Nocturnal Hemoglobinuria. One-third of patients with PNH experience at least one thromboembolic event during the course of the disease, with thrombosis being the most common cause of death in these patients. The mechanism of thrombosis in PNH is complex and continues to be of great research interest. Since the introduction of C5 complement inhibitors in the treatment of PNH, the incidence of thromboembolic events has decreased substantially. We retrospectively analyzed data concerning the thrombotic episodes of 41 patients with PNH from 14 different national hematology centers in Greece. Sixteen patients (39%) experienced at least one episode of thrombosis, including, seven (43.8%) at diagnosis, seven (43.8%) during the course of the disease and two (12.5%) patients prior to PNH diagnosis. Nearly half of these individuals (n=7, 43.8%) had multiple episodes of thrombosis during the course of their disease. The most common sites of thrombosis were intra-abdominal veins. Three out of 26 patients developed thrombosis while on eculizumab. In none of the 16 patients, the thrombotic event was fatal. Our findings, despite the small number of patients, confirmed that thrombosis continues to be a significant complication of PNH affecting more than one third of the patients.